Effects of external perturbations on dynamic performance of carbon dioxide transcritical power cycles for truck engine waste heat recovery. (15th November 2018) - Li, Xiaoya; Tian, Hua; Shu, Gequn; Hu, Chen; Sun, Rui; Li, Ligeng
Abstract: Carbon dioxide transcritical power cycle (CTPC) systems are dynamically tested on a constructed test bench using an expansion valve. Effects of external perturbations of pump speed, expansion valve opening and engine conditions on dynamic performance of the CTPC systems are investigated with step changes. Dynamic characteristics are identified with rise time, settling time and overshoot. Results show that both a basic CTPC system and a CTPC system with a recuperator (R-CTPC) behave as a second-order underdamped system with the perturbations of pump speed and expansion valve opening. Overshoot or undershoot tends to appear in pressures when pump speed changes, while overshoot or undershoot occurs more noticeably in temperatures when expansion valve opening varies. Although the CTPC systems respond slowly with the perturbations of engine conditions, they have the ability to operate safely and produce power continuously. Therefore, the CTPC systems are robust when facing narrow fluctuations of heat sources while swift when required to make adjustments, showing great potential for truck engine waste heat recovery. Overall, current research gives a full understanding of the dynamic performance of the CTPC systems, which will provide references for dynamic model validation and possible control strategy identification. Highlights: Perturbations include pump speed, expansion valve opening, engine speed and torque. Effects on dynamic performance of CTPC and R-CTPC are tested with step changes. CTPC systems behave as a second-order underdamped system and overshoot occur. CTPC systems respond fast with variations of pump speed and expansion valve opening. CTPC systems are robust facing narrow fluctuations while swift when needs to adjust.